Administrative Services in Ampreng Village, Langowan Barat Subdistrict, Minahasa Regency - Itje Pangkey; Grafita F. Manampiring; Novel Assa; Ellen Eva Polii; Jeneman Lanawaang (Technium Social Sciences Journal, 2024)
This research aims to find out how to analyze and describe administrative services in the village of Ampreng, West Langowan district of Minahasa. The research method used is descriptive dermatative. The number of informants in this study is six. Data collection using observation, interview and documentation techniques. Data analysis through Data Reduction, Data Presentation and Conclusion Drawing. The results of the research show that the transparency of administrative services in the village of Ampreng district of West Langowan has not been maximized due to the lack of information boards on the conditions sto be met by the community. The village government is not open about the duration of service so the village people have to go back and forth to check whether the necessary letters have been completed or not 2. The accountability of the services provided is not maximum because the village government has no responsibility in running because often the government of the village is not in place when the farmers need services 3. The service products provided are not maximum this is because the facilities available in the village office are not sufficient to support the implementation of administrative services.